2021
DOI: 10.4102/ajod.v10i0.827
|View full text |Cite
|
Sign up to set email alerts
|

African families’ and caregivers’ experiences of raising a child with intellectual disability: A narrative synthesis of qualitative studies

Abstract: African families' and caregivers' experiences of raising a child with intellectual disability: A narrative synthesis of qualitative studies', African Journal of Disability 10(0), a827.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…Existing literature shows that caregivers of children with developmental disabilities report more negative experiences than caregivers of children without developmental disabilities, and that this is exacerbated in low-income settings [ 29 ]. This includes caregiver mental health problems such as depression and anxiety [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature shows that caregivers of children with developmental disabilities report more negative experiences than caregivers of children without developmental disabilities, and that this is exacerbated in low-income settings [ 29 ]. This includes caregiver mental health problems such as depression and anxiety [ 30 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the rearing of any child by the family requires support and availability of resources (McKenzie & McConkey 2016 ). South Africa is one of the upper middle-income countries where the majority of black African families continue to live in poverty and lack of specialised services for ID (Mkabile et al 2021 ). Few studies have been conducted on support experiences of families of children with ID in South Africa and little is known about the survival of these families to cater for the needs of their children with ID.…”
Section: Introductionmentioning
confidence: 99%
“…Despite substantial attention paid to stigma towards people with mental health conditions (Lauber et al, 2003; Morgan et al, 2018), equivalent research in the field of ID has been limited, particularly in low and middle‐income countries (Jansen‐van Vuuren & Aldersey, 2020; Scior, Potts, & Furnham, 2013; Wang et al, 2021). Cross cultural studies have exposed differences in the level of awareness of ID and desire of social distance among lay people from different sociocultural backgrounds (Jansen‐van Vuuren & Aldersey, 2020; McConkey et al, 2021; Mkabile et al, 2021). Research has suggested that stigmatisation is more prominent in cultures with a collectivist ethos that tend to avoid emotional expressions to maintain the family's reputation (Scior, Potts, & Furnham, 2013).…”
Section: Introductionmentioning
confidence: 99%